Teenagers on TikTok: Play, Mimesis, and “Digital Authority” - N.K. Radina (Социальная психология и общество)
Context and relevance. This article is based on the analysis of an empirical study of viral videos of the Russian-language segment of the digital social platform TikTok. The productivity of the theoretical schemes proposed by M.Yu. Kondratiev for studying the psychology of teenagers using digital communication is discussed. The key ideas are M.Yu. Kondratiev's ideas about play, authority, and the characteristics of growing up in a mono-structured teenagers group. Objective. The objective is to analyze the results of an empirical study using TikTok in the context of M.Yu. Kondratiev's ideas about the role of play, authority, and the characteristics of growing up in a mono-structured teenagers group. Hypothesis. The research question is based on the assumption of the universality and heuristic nature of the theoretical schemes used by M.Yu. Kondratiev to characterize teenagers. Methods and materials. The praxis method, a method for analyzing the products of activity, is used as a method for collecting and analyzing empirical data. The research materials were extracted from the Russian-language segment of the digital social platform TikTok (a digital resource for video sharing). The initial sample was 2520 videos, then 215 “viral videos” with high usage rates (views, approvals, forwards, comments) were selected. Results. It turned out that some of the viral videos contain topics typical for teenagers – about school life, exams, videos demonstrating repetition games, etc. It is concluded that the teenage group takes an active part in the formation of a pool of viral videos in the Russian-language segment of TikTok. Based on the obtained results, the relevance of M.Yu. Kondratiev's ideas regarding teenagers' communications on digital communication platforms with strong algorithmic support is discussed. Conclusions. It is concluded that playing on TikTok exists as a phenomenon relevant to the tasks of teenagers' age development; TikTokers' authority is algorithms (artificial intelligence that regulates digital communication), and TikTok, when used rationally, can compensate for the problems of growing up in a mono-structured group.